2004
DOI: 10.1160/th04-03-0165
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal hormone replacement and venous thromboembolism following hip and knee arthroplasty

Abstract: Hormone replacement therapy has been associated with venous thromboembolism. Controversy exists regarding the appropriate management of hormone replacement in the perioperative setting and in other situations--such as acute illness--predisposing to acute venous thromboembolism. We performed a case-control study to determine whether perioperative hormone replacement is associated with venous thromboembolism following hip and knee arthroplasty. 108 patients with postoperative venous thrombosis were matched by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…A recent case-control study with 108 cases and 210 controls found no association between perioperative HRT use and postoperative venous thromboembolism. 9 At The Cleveland Clinic's IMPACT (Internal Medicine Preoperative Assessment, Consultation, and Treatment) Center and at many other institutions across the country, patients are typically seen 1 to 2 weeks before surgery. In that situation, the prothrombotic state that HRT produces is not going to dissipate if the patient stops the drug 1 week prior to surgery; this prothrombotic state actually takes a few weeks to dissipate.…”
Section: ■ Case 2: Nsaid Use and Hormone Replacement Therapy In A Hipmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case-control study with 108 cases and 210 controls found no association between perioperative HRT use and postoperative venous thromboembolism. 9 At The Cleveland Clinic's IMPACT (Internal Medicine Preoperative Assessment, Consultation, and Treatment) Center and at many other institutions across the country, patients are typically seen 1 to 2 weeks before surgery. In that situation, the prothrombotic state that HRT produces is not going to dissipate if the patient stops the drug 1 week prior to surgery; this prothrombotic state actually takes a few weeks to dissipate.…”
Section: ■ Case 2: Nsaid Use and Hormone Replacement Therapy In A Hipmentioning
confidence: 99%
“…Several experts feel that routine HRT discontinuation may be unnecessary in patients receiving appropriate pharmacologic antithrombotic prophylaxis. 9…”
Section: ■ Case 2: Nsaid Use and Hormone Replacement Therapy In A Hipmentioning
confidence: 99%
“…This study is a secondary analysis of a study that examined risk factors for postoperative VTE in postmenopausal women (≥50 years), particularly the relationship between hormone replacement therapy and postoperative VTE. 22 Cases were identified by searching the CCF International Classification of Diseases, Ninth Revision database for women older than 50 years who underwent hip or knee arthroplasty between January 1997 and July 2002. Total, partial, and revision elective arthroplasty were included for both joints.…”
Section: Search Strategymentioning
confidence: 99%
“…The two studies concluded that HRT administration had no effect on mortality or morbidity rates in women undergoing vascular surgery. One case–control study found no association between perioperative HRT and post‐operative thrombosis in patients undergoing major orthopaedic surgery (19).…”
Section: Resultsmentioning
confidence: 99%
“…Extrapolated evidence form one cohort study (17) (evidence level 2 ++ ) and from one case–control study (19) (evidence level 2 + ) recommend continuation of HRT in the perioperative period with strength classification of C. However, the formal consensus panel defended withdrawal of HRT before surgery, because of higher risk of thromboembolism with this therapy compared with OC. Oestrogen dosages in HRT are higher and the target population is older.…”
Section: Resultsmentioning
confidence: 99%